PENGGUNAAN DIGITAL BOOK BERBASIS ANDROID UNTUK MENINGKATKAN MOTIVASI DAN KETERAMPILAN MEMBACA PADA PELAJARAN BAHASA ARAB - Muhammad, Mumu; Rahadian, Dian; Safitri, Erna Retna (PEDAGOGIA, 2017)
Media utilization technology as supporting learning activities more open. Good learning can be supported from a conducive learning environment as well as the communication link between teachers, students can run well. The learning process will be effective when utilizing the various facilities and infrastructure provided includes utilizing a variety of media study. Ironic when the rapid technological developments, the tendency of the learning process that occurs at this time are mostly conventional learning monotonous so it is not able to explore the potential of students and only pose a stiff learning makes students feel bored during the course of the learning process. To solve the above problems, the teacher should be able to create a state of active learning, creative, effective and fun. The integration of the learning process of students with the teacher's teaching has led to an instructional activities that harmony does not come alone but through the settings using the media as one of support in learning activities, one of the efforts undertaken in this study is the use of media android as a learning medium to increase motivation and reading skills of students in learning Arabic.This study uses a quasi-experimental method with de`esain study is a non-equivalent control group pre-test and post-test design, using two-class as an experimental class and control class. Begins by providing an early test to identify students' mastery of skills. Then implemented learning by using media digital books in the experimental class and ordinary classroom learning control. After learning is completed the final test to identify students 'motivation, improved reading skills and to measure students' reading skills. Then the data obtained were analyzed with statistical analysis.The results showed that the use of digital media android based eBook positive effect on student motivation and positive influence on the improvement of students' reading skills in learning Arabic sub subject Bidayatul Faizin I'rob in high school.